Analysis of the use of open tasks in learning process in students of 10th class C at Unidad Educativa Fernando Daquilema during the academic period 2017-2018. - Guevara Rodriguez, Carlina Julissa (2018)
This research project was carried out in the Unidad Educativa "Fernando Daquilema", located in the City of Riobamba, Province of Chimborazo, with the collaboration of the teacher and the students of the Tenth Year of Basic Education "C", during the Period Academic 2017-2018. The population is composed of 37 students and 1 teacher, being 18 children and 19 girls. The main purpose of this research is to describe the use of Open Tasks to facilitate and improve the learning process of the English Language. There are several types of research but was applied descriptive with a qualitative approach because it about knows the facts, processes, structures and people in their totality through the interaction between the researcher and the subjects they study. The methods used were Deductive and Inductive to be able to interpret in a better way and analyze the whole process through the observation that the technique was applied to the students mentioned above, in the different classes of the subject of English and to determine which are the existing difficulties in learning the language and thus develop this research. The data collection instrument (Observation Guide) was designed in the best way considering the characteristics of the subject to obtain data that was identified whether the Teacher uses Open Tasks or not to teach the English language. This research is important because it was observed that the Teacher does not correctly apply the Open Tasks because she uses more the teacher guide book.